2021
DOI: 10.1155/2021/8072126
|View full text |Cite|
|
Sign up to set email alerts
|

TAP Test Image Dynamic Tracking Study after Thyroid Cancer Surgery and after Radiotherapy and Chemotherapy

Abstract: Thyroid cancer is a relatively common endocrine gland malignant tumor; if improper treatment, there will be a high risk of recurrence or metastasis, and abnormal sugar chain glycoprotein (TAP) has a close relationship with the development of the disease; therefore, the purpose of this article is to discuss abnormal sugar chain glycoprotein (TAP) as thyroid cancer curative effect evaluation and radiation and chemotherapy after surgery clinical significance. In this paper, 95 patients with thyroid cancer diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%